Babies [videorecording (DVD)] - Balmès, Thomas (Universal, 2010)
Follows four babies from different parts of the globe as they navigate their first year of life. Features Ponijao from Namibia, Bayarjargal from Mongolia, Hattie who lives in San Francisco, and Mari from Tokyo.